Thermodynamic design optimisation of an open air recuperative twin-shaft solar thermal Brayton cycle with combined or exclusive reheating and intercooling. (15th September 2017) - Meas, M.R.; Bello-Ochende, T.
Abstract: The present work applies the method of entropy generation minimisation to investigate the effects of reheating and intercooling on the optimal design and maximum net power output of an open recuperative solar thermal Brayton cycle. Three cases are considered. The intercooled cycle demonstrates both the greatest net power output per unit collector area and the highest ratio of total irreversibility to heat input, followed by the combined and reheated cycles, respectively. Temperature differences across the components are identified as the primary cause of entropy generation. The receivers are found to be the primary site of entropy generation in all cases, and entropy generation in the intercoolers found to constitute the smallest proportion of the total entropy production rate. The optimised heat exchanger lengths are shown to lie on the maximum constraints, and the channel cross-sections found to constrict with increasing mass flow rate such that the total plate surface area is increased to promote heat transfer. The receiver and reheater geometric parameters are found to vary such that the absorber tube surface temperatures are kept below the maximum constraint, and the trends in the optimal parameters for receivers and reheaters comprising circular cross-section absorber tubes found to fluctuate considerably.